Intradermal administration of RiVax protects mice from mucosal and systemic ricin intoxication - Marconescu, Praveena S. (2010)
Ricin toxin is a CDC level B biothreat. We have developed a ricin vaccine, RiVax, which is a recombinant mutant of ricin A chain. RiVax is safe, immunogenic and protective in mice when administered intramuscularly (IM). We have now attempted to increase the utility and immunogenicity of RiVax by administering it intradermally (ID) with or without alum. Without alum, Rivax administered by the ID and IM routes was equally immunogenic and protective. With alum, ID vaccinations were more immunogenic and protective against both systemic and mucosal challenge with ricin and superior in protecting animals from ricin-induced lung damage.